2014
DOI: 10.1186/1471-2458-14-852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cost-effectiveness of preventive zinc supplementation

Abstract: BackgroundEven though the WHO currently recommends zinc for diarrhea management, no consensus has been reached with respect to routine distribution of zinc for preventive reasons. We reviewed the health impact of preventive zinc interventions, and evaluated the relative cost effectiveness of currently feasible interventions.MethodsUsing the latest relative risk estimates reported in the literature, we parameterized a health impact model, and calculated the expected benefits of zinc supplementation in a represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…Preventative supplementation ( Edejer et al , 2005 ; Ma et al , 2008 ; Bhutta et al , 2013 ; Fink and Heitner, 2014 );…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Preventative supplementation ( Edejer et al , 2005 ; Ma et al , 2008 ; Bhutta et al , 2013 ; Fink and Heitner, 2014 );…”
Section: Resultsunclassified
“… Fink et al (2014) estimated an incremental cost of $606–1211 per DALY averted for preventive supplementation interventions vs doing nothing. However, it was not clear whether health system costs were also included or not.…”
Section: Resultsmentioning
confidence: 99%
“…While a number of studies have examined the cost-effectiveness for preventing diarrhoea (Robberstad et al, 2004;Mejia et al, 2015;Shillcutt et al, 2017), these studies have been performed in the context of therapeutic zinc supplementation, and the outcomes for prophylactic zinc may differ. In addition, the few cost-effectiveness studies for prophylactic zinc have been conducted among children older than 6 months of age (Brown et al, 2013;Chhagan et al, 2013;Fink and Heitner, 2014) and none have been performed using data from East Africa. This study was therefore conducted to fill the knowledge gap with regards to the cost-effectiveness of prophylactic zinc supplementation in preventing various forms of diarrhoea in children aged between 6 weeks and 18 months in an east African setting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For both outpatient and hospitalbased care, cost inputs included provider costs (medications and service provision), and costs borne by caregivers (out-of-pocket spending and productivity losses). Sources of cost data included secondary cost data from WHO-CHOICE (WHO, 2019) and similar studies (Robberstad et al, 2004;Tate et al, 2009;Brown et al, 2013;Fink and Heitner, 2014;Ruhago et al, 2015;WHO, 2019). Input values and sources are shown in Table 1.…”
Section: Cost Of Zinc Supplementation and Care For Diarrhoeal Illnessmentioning
confidence: 99%
“…In recent decades, several relatively affordable crops and condiments (such as grains, potatoes, oil, salt, and soy sauce) have been put forward as ideal carriers of micronutrients to improve public health cost‐effectively through food fortification or biofortification, providing abundant solutions for alleviating zinc deficiencies in underdeveloped areas. Numerous studies around the world have shown that zinc supplementation, food fortification, and biofortification are highly cost‐effective (Fink & Heitner, 2014; Horton, 2006; Ma et al, 2008; Mejía et al, 2015; Stein et al, 2007; Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%